Effect of monospecific antibodies against baltergin in myotoxicity induced by Bothrops alternatus venom from northeast of Argentina. Role of metalloproteinases in muscle damage - Gay, Claudia Carolina (2013)
Myotoxicity, one of the most relevant local manifestations in envenomation by Bothrops genus, may result from a direct action of myotoxins or be due to an indirect vascular degeneration and ischemia. Baltergin, a snake venom metalloproteinase (SVMP), isolated from Bothrops alternatus venom has been used to obtain monospecific IgG, in order to determine the relative role of toxin in myotoxicity induced by whole venom. Bothrops diporus venom, another medical relevant genus of the northeastern region of Argentina, was also studied. Anti-baltergin IgG was able to neutralize completely the hemorrhagic activity of B. alternatus venom at an antibodies:venom ratio of 30:1 (w:w). However, mice injected with B. diporus venom showed a small spot remaining even at the highest ratio of IgG:venom assayed (50:1; w:w). Specific antibodies were efficient to neutralize the myotoxicity of B. alternatus venom at ratio 30:1 (w:w) but did not neutralize the same effects in B. diporus venom. Anti-baltergin polyclonal antibodies were useful tools for revealing the central role of SVMPs in the development of myotoxicity of B. alternatus venom, as well as, helping to suggest indirectly presence of potent myotoxic phospholipases A2 (PLA2s) in B. diporus venom.